Keragaman Somaklonal untuk Perbaikan Tanaman Artemisia (Artemisia annua L.) melalui Kultur In Vitro - Endang G Lestari; Ragapadmi Purnamaningsih; Muhammad Syukur; Rosa Yunita (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2010)
Somaclonal Variability for the Improvement of PlantsArtemisia (Artemisia annua L.) by In Vitro Culture.Endang G. Lestari, Rosa Yunita, and Ali Husni. Artemisiaannua L., a family member of Asteraceae, is medicinalplants originated from China. The plant has been widelyused by the local people for malaria remedy. Its active substance,artemisine, has been proved to hamper the malariabacteria incubation, Plasmodium sp. In accordance with theWHO recomendation, the Department of Health of Indonesiais now in the attempt of developing this plant as thesubtitute of chloroquin because of the malaria bacteriaresistance to this antidote. In Indonesia, the artemisinecontent of the plant less than 0,5% is the crucial problemleading no investors are interested in its economic value.Therefore, Indonesian Medicinal and Spice Crops ResearchInstitute; BPTO Tawangmangu, Indonesian Institute ofSciences; and PT Kimia Farma cooperate for obtaining theprime clone by breeding, selection, as well as environmentaladaptation. In coping with the problem, ICABIOGRAD in thecollaboration with Bogor Agricultural University haveconducted the research for genetic improvement throughmutative induction and field selection. This research onsomaclonal variation. was conducted from Januari 2006 toJuni 2008. Eksplan used for experiment were shoots radiatedwith 10-100 Gy gamma ray. The result showed that the shootradiated with the dosage of 70-100 Gy was unable to grow.On the other hand, the high level of multiplication wasacquired in the one radiated with 10-30 Gy. The optimumradiation for somaclonal radiation was eventually gainedwith 40-60 Gy. The somaclone lines with 10-60 Gy radiationhave been aclimatized and planted in Gunung Putri plot inthe elevation of 1545 asl. Artemisinin content at the highbiomases genotype is 0,49-0,52%.